Prognostic immune markers identifying patients with severe COVID-19 who respond to tocilizumab - De Biasi, Sara; Mattioli, Marco; Meschiari, Marianna; Lo Tartaro, Domenico; Paolini, Annamaria; Borella, Rebecca; Neroni, Anita; Fidanza, Lucia; Busani, Stefano; Girardis, Massimo; Coppi, Francesca; Mattioli, Anna Vittoria; et al. (Frontiers in Immunology, 2023)
A growing number of evidences suggest that the combination of hyperinflammation, dysregulated T and B cell response and cytokine storm play a major role in the immunopathogenesis of severe COVID-19. IL-6 is one of the main pro-inflammatory cytokines and its levels are increased during SARS-CoV-2 infection. Several observational and randomized studies demonstrated that tocilizumab, an IL-6R blocker, improves survival in critically ill patients both in infectious disease and intensive care units. However, despite transforming the treatment options for COVID-19, IL-6R inhibition is still ineffective in a fraction of patients. In the present study, we investigated the impact of two doses of tocilizumab in patients with severe COVID-19 who responded or not to the treatment by analyzing a panel of cytokines, chemokines and other soluble factors, along with the composition of peripheral immune cells, paying a particular attention to T and B lymphocytes. We observed that, in comparison with non-responders, those who responded to tocilizumab had different levels of several cytokines and different T and B cells proportions before starting therapy. Moreover, in these patients, tocilizumab was further able to modify the landscape of the aforementioned soluble molecules and cellular markers.